Assessing the Consultation and Relational Empathy (CARE) Measure in sexual health nurses' consultations. Issue 1 (December 2017) - Bikker, Annemieke; Fitzpatrick, Bridie; Murphy, Douglas; Forster, Lorraine; Mercer, Stewart
Abstract Background Increasingly healthcare policies emphasise the importance of person-centred, empathic care. Consequently, healthcare professionals are expected to demonstrate the 'human' aspects of care in training and in practice. The Consultation and Relational Empathy (CARE) Measure is a patient-rated measure of the interpersonal skills of healthcare practitioners. It has been widely validated for use by healthcare professionals in both primary and secondary care. This paper reports on the validity and reliability of the CARE Measure with sexual health nurses. Methods Patient questionnaires were collected for 943 consultations with 20 sexual health nurses. Participating patients self-completed the questionnaire immediately after the encounter with the nurse. The questionnaire included the ten item CARE Measure, the Patient Enablement Index, and overall satisfaction instruments. Construct validity was assessed through Spearman's correlation and principal component analysis. Internal consistence was assessed through Cronbach's alpha and the inter-rater reliability through Generalisability Theory. Data were collected in 2013 in Scotland. Results Female patients completed 68% of the questionnaires. The mean patient age was 28.8 years (standard deviation 9.8 years). Two of the 20 participating nurses withdrew from the study. Most patients (71.7%) regarded the CARE Measure items as very important to their consultation and the number of 'not applicable' and missing responses' were low (2.6% and 0.1% respectively). The participating nurses had high CARE Measure scores; out of a maximum possible score of 50, the overall mean CARE measure score was 47.8 (standard deviation 4.4). The scores were moderately correlated with patient enablement (rho = 0.232, p = 0.001) and overall satisfaction (rho = 0.377, p = 0.001. Cronbach's alpha showed the measure's high internal consistency (Cronbach's alpha coefficient = 0.95), but the inter-rater reliability could not be calculated due to the high achieved CARE Measure scores that varied little between nurses. Conclusions Within this clinical context the CARE Measure has high perceived relevance and face validity. The findings support construct validity and some evidence of reliability. The high CARE Measure scores may have been due to sample bias. A future study which ensures a representative sample of patients on a larger group of nurses is required to determine whether the measure can discriminate between nurses.